Infants' perception of lightness changes related to cast shadows - Sato, Kazuki (PLoS One, 2017)
When humans perceive the lightness of an object’s surface in shadows there is an implicit assumption that cast shadows dim the surface. In two experiments, we investigated whether 5- to 8-month-old infants make this assumption about shadows. According to this shadow assumption, the apparent change in lightness produced by shadows on an object’s surface are attributed to blocked light sources. If infants can use the shadow assumption to perceive the object’s lightness in shadows, they will also be able to detect unnatural lightness changes in shadows. We compared the infants’ looking times to the unnatural and the natural lightness changes in the shadow when an object (duck) goes through the cast shadow. In Experiment 1, we examined whether infants could detect the unnatural lightness changes of the object’s surface in shadows. We created computer-graphic movies of unnatural and natural lightness changes to the duck’s surface. Our results showed that 7- to 8-month-olds but not 5- to 6-month-olds significantly preferred the movie with the unnatural changes in lightness, indicating that only the older infants could detect these changes. In Experiment 2, we confirmed that the infants’ preference was based on the detection of unnatural lightness changes according to the shadow assumption. The natural and the unnatural lightness changes of Experiment 1 were presented without cast shadows. Under these conditions, neither younger nor older infants showed a significant preference. Taken together, the experiments showed that 7- to 8-month-old infants could detect the unnaturalness of a surface’s lightness changes produced by shadows. In conclusion, our findings suggest that 7- to 8-month-old infants can perceive an object’s lightness in shadows by using an assumption that cast shadows dim the surface of an object.